Alcohol Brief Interventions (ABIs) for male remand prisoners: protocol for development of a complex intervention and feasibility study (PRISM-A). Issue 4 (4th May 2017) - Holloway, Aisha; Landale, Sarah; Ferguson, Jennifer; Newbury-Birch, Dorothy; Parker, Richard; Smith, Pam; Sheikh, Aziz
Abstract : Introduction: In the UK, a significant proportion of male remand prisoners have alcohol problems. Alcohol Brief Interventions (ABIs) are an effective component of a population-level approach to harmful and hazardous drinking. ABIs have been shown to reduce the aggregate level of alcohol consumed and therefore reduce harm to the individual and to others. However, in relation to remand prisoners, there is no evidence as to how effective ABIs could be. The aims of this study are therefore to explore the feasibility and acceptability of an ABI for adult male remand prisoners and to develop an ABI for this group to be piloted in a future trial. Methods and analysis: The study will comprise three stages. Stage 1: a cross-sectional survey of adult male remand and convicted prisoners (n=500) at one Scottish prison and one English prison will be undertaken to assess acceptability and feasibility of delivering an ABI, as well as prevalence rates of harmful, hazardous and dependent drinking. Stage 2: in-depth interviews will be conducted with a sample of remand prisoners (n=24) who undertook the survey (n=12 in Scotland; n=12 in England). Two focus groups (one in Scotland and one in England) with six to eight key stakeholders associated with alcohol-related healthcare provision in prisons will be conducted to explore views on barriers, facilitators and levers to ABI delivery. Stage 3: through formal intervention mapping, the analysed data will inform the refinement of an acceptable ABI that is feasible to deliver to male remand prisoners. Ethics and dissemination: The project has been approved by the National Research Ethics Committee (NRES), National Offender Management System, Health Board Research and Development, Scottish Prison Service and ethics committee at The University of Edinburgh. Results will be published in peer-reviewed journals and presented at local, national and international conferences.